Efektivitas Program Penyediaan Air dan Sanitasi Berbasis Masyarakat di Jorong Sawah Kareh Nagari Balimbing Kecamatan Rambatan Kabupaten Tanah Datar - Edo Satrio Wahyudi; Erna Juita; Elvi Zuriyani (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
This research aims to obtain data, process, analyze and discuss the Jorong Sawah Kareh Regional PAMSIMAS Program seen from: 1) to find out how many people have received clean water 2) to find out the community's efforts to get clean water as a whole. The population in this research was carried out in Jorong Sawah Kareh. The technique used for this research was qualitative. The final results of this research reveal that: 1) The PAMSIMAS program which was held in Jorong Sawah Kareh Nagari Balimbing, Rangkat District, Tanah Datar Regency so that the local community gets clean water so that it reaches residents' homes which is suitable for consumption, both for cooking, drinking, cooking, and so forth. 2) Nagari Government's efforts to ensure that people get drinking water or clean water that is suitable for consumption in Jorong Sawah Kareh. Therefore, the Nagari Government is giving an appeal to the community to save water so that not a lot of water is wasted and can use the PAMSIMAS water in moderation and not excessively.